Randomized Control Trial of 3% Nebulized Hypertonic Saline in Reducing the Length of Hospital Stay in Children with Bronchiolitis (Journal of Rangpur Medical College, 2023)
Background: Bronchiolitis is the most common cause of lower respiratory tract infections within the first 2 years of life. Despite tantalizing efforts, an effective optimized treatment for bronchiolitis still remains elusive. Nebulized hypertonic saline may improve clinical severity scores and reduce length of hospital stay among infants with non-severe acute bronchiolitis.Objective: The objective of this study was to evaluate efficacy of 3% hypertonic saline in reducing the length of hospital stay in children with bronchiolitis.Method: This randomized control trial was conducted in the department of Paediatrics, Rangpur Medical College Hospital between July 2018 to June 2020. After acceptance and ethical clearance, 72 infants and young children fulfilling the selection criteria were enrolled into this study. Children were randomly divided into two groups, designed as group–A and group–B. Patients in group A were nebulized with 3% hypertonic saline and group B with normal saline. Patients in each group were nebulized three times 8 hourly during hospital stay. Each group received the same standard supportive measures. Data was analyzed through SPSS (version 23.0) software using chi-square test, student t' test, where applicable. Statistical significance was set as 0.05 level.Results: Among the 72 children, 72.22% (26/36) of group A and 58.33% (21/36) of group B were male, with a male female ratio of 1.88:1. Mean age of the children of group A (7.5±1.94 months) was significantly higher than that of group B (5.8±2.01 months) (p=0.032). Baseline clinical characteristics were almost similar, except oxygen saturation (p